Anticancer potency of black sea cucumber (Holothuria atra) from Mentawai Islands, Indonesia - Satari, Mieke Hemiawati; Arma, Utmi; Ilyas, Syafruddin; Handayani, Dian (Padjadjaran Journal of Dentistry, 2017)
Introduction: The source of bioactive compounds believed to have strong anticancer potency is derived from sea cucumber. Black sea cucumber (Holothuria atra) is a dominant species in Mentawai Islands, West Sumatera, Indonesia. Key factor compound that acts as anticancer in sea cucumber extract is tritepenoid also known as Frondoside A. The purpose of this study was to determine the effectiveness of the active compound taken from black sea cucumber as anticancer. Methods: Methods used was experimental laboratory. Anticancer activity of black sea cucumber was determined by using the MTT assay cytotoxic test to measure the IC50. Cytotoxic test was conducted with Supris clone-1 (SP-C1) derived from cloned lymphadenopathy of patients with oral squamous cell carcinoma on lingual part. Results: It was found that the compounds contained in black sea cucumber has strong anticancer activity (IC50 = 5.25 Î¼L/mL) against SP-C1. Conclusion: Black sea cucumber extract has strong cytotoxic effects against cancer cells SP-C1, therefore black sea cucumber extract potentially developed as a new source of cancer medicine.